New data on one of the first plesiosaur (Reptilia, Sauropterygia) skeletons recovered from Antarctica, with comments on the dorsal and sacral regions of elasmosaurids - O'gorman, Jose Patricio; Aspromonte, Franco Roger; Reguero, Marcelo Alfredo (Alcheringa: An Australasian Journal of Palaeontology)
Elasmosaurids are among the most frequently recorded marine reptile fossils from the Campanian–Maastrichtian strata of Antarctica. Here, we describe one of the earliest quarried specimens, MLP 82-I-28-1, which is identified as a non-aristonectine elasmosaurid and phylogenetically nested within Weddellonectia. An ancestral states analysis of dorsal and sacral vertebral counts suggests that weddellonectian elasmosaurids plesiomorphically possessed between 17 and 18 dorsal vertebrae. The comparatively high count of 24 dorsal vertebrae observed in aristonectine elasmosaurids, such as Aristonectes quiriquinensis, thus likely represents a derived state correlated with the acquisition of larger body size. Fil: O'gorman, Jose Patricio. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina Fil: Aspromonte, Franco Roger. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina Fil: Reguero, Marcelo Alfredo. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina